Randomized, controlled trial testing the effectiveness and safety of 2.5% and 5% benzoyl peroxide for the treatment of pitted keratolysis - Charussri Leeyaphan (2022)
Background: The appropriate dosage and duration of topical benzoyl peroxide gel (BP) treatment of pitted keratolysis (PK) is controversial. Objective: To compare the effectiveness and safety of topical 2.5% and 5% BP for the treatment of PK. Materials and methods: This randomized, controlled trial was conducted at Chumpol Naval Rating School, Chonburi, Thailand. Naval rating cadets with PK were randomly assigned to either a 2.5% or a 5% BP group and were requested to apply the related medication on each sole once daily, for 2 weeks. Results: All 42 and 47 participants who were treated with 2.5% and 5% BP, respectively, were included in the later analysis. Self-evaluation of the foot odor level using a visual analog scale (VAS) showed significant decreases for both groups (p<.001). The pitted lesions were evaluated by dermatologists and found to have improved in the 2.5% and 5% BP groups (69.0% versus 63.8%, respectively; p=.457). Side effects did not statistically differ between the two groups (p>.05). Conclusions: Either 2.5% or 5% BP can be used for the treatment of PK and foot malodor. Due to the similarities in their efficacies and side effects, the use of 2.5% BP may be preferable.